Analisis Penggunaan Google Classroom dalam Pembelajaran Renang di Massa Pandemic Covid-19 Pada Siswa SMP IT AL-ISTIQOMAH - Rochmat Waluyo; Resty Gustiawati; Rhama Nurwansyah (Peneliti.net, 2021)
This study aims to determine the learning process of the Google Classroom in the COVID-19 pandemic era, the solar system material, to determine students' perceptions of the implementation of the Google Classroom learning in the COVID-19 pandemic era, the Swimming material, to determine the teacher's perception of the implementation of the Google Classroom learning in the COVID-19 pandemic era. swimming material. This type of research uses a qualitative approach, the data sources in this study include primary and secondary data sources. In data collection techniques, researchers used the methods of observation, interviews, and documentation. Data analysis in this study uses data flow model analysis by Miles and Huberman. Checking the validity of the data with credibility (trustworthiness), transferability (transferability), dependanility (dependence), confirmability (certainty). The results of this study conclude that (1) Google classroom learning in the COVID-19 pandemic era swimming material for class VII SMP IT Al-Istiqomah has not succeeded in achieving the KKM classically. (2) Students' perceptions of the implementation of the google classroom learning in the COVID-19 pandemic era, swimming material, there is no practicum on swimming material (3) The teacher's perception of the implementation of physical education learning with the google classroom media in the COVID-19 pandemic era, swimming material, students' understanding of the material will be different when face-to-face as in a school building, and student discipline is still lacking.